A financeirização do agronegócio do café no Brasil: a trama do capital fictício na produção capitalista do espaço - Novais, Weldon Pereira Silva de (2023)
The main objective of the present work was to understand how financialization manifested itself in the coffee agribusiness today, with emphasis on the stages of commercialization in the Brazilian production and processing of this bean. The business responses presented in the café, the investigation process, support the investigation that financialization in agribusiness in Brazil is configured by financial stock exchanges and by the outstanding performance in the main foreign financial institutions and by the performance in the main foreign financial institutions in the country. Financial investors have made them the main agents of this financial economy, given that roasters and financial investors, with the profit from the publicly traded operation to maximize investors. The rise of the finances of these companies/acquisitions strengthen the results of the merger processes, the monopolization and centralization of the coffee market by roasters and global exporters. The method of interpretation assumed in this work was materialism - historical - dialectical. Bibliographic/documentary collection and field study were used as methodological procedures for research data and information on national and international coffee.